HUBUNGAN KADAR NIKOTIN ROKOK DENGAN TEKANAN DARAH PADA MAHASISWA (Studi Pada Mahasiswa Perokok Asrama Daerah Kalimantan Barat) - Fhoka, Finanda; Trisnawati, Elly; Pradana, Tedy Dian (JUMANTIK (Jurnal Mahasiswa dan Peneliti Kesehatan), 2015)
Smoking is an important issue today. Smoking kills nearly six million people a year five million active smokers and passive smokers 600,000. One person dies every six seconds due to tobacco (WHO, 2013). Cigarettes contain nicotine can increase blood pressure. According to WHO, about 972 million people globally have hypertension (â‰¥140 / 90 mmHg). This figure is likely to rise to 29.2% in 2025. The prevalence of hypertension in Indonesia in 2013 reached 31.7% of the population aged â‰¥18 years and West Kalimantan prevalence of hypertension of 28.3%, while the Pontianak city reached 27 337 cases of hypertension cases , The study aims to determine the relationship of smoking with the nicotine levels in the blood pressure of students (studies on smokers student dormitory area of West Kalimantan). The design of this study was observational analytic with cross sectional sample of 86 people. Sampling with proportional random sampling method and analyzed using statistical test Chi square. Research results show that there is a relationship between nicotine levels (p value = 0.000, PR = 3.69) and caffeine (p value = 0.001, PR = 1.97) with blood pressure in students. Variables that no relationship between physical activity (p value = 1.000, PR = 0.84) and the level of stress (p value = 0.506, PR = 0.75). The manager of the hostel and its citizens are advised to apply the rules Perda No. 10 of 2010 on No Smoking (KTR).Keywords: Nicotine levels, blood pressure, Dormitory area